Quaternary ammonium‐functionalized polymers in biodegradable matrices: Physicochemical properties, morphology, and biodegradability. Issue 37 (30th May 2017) - Belkhir, Kedafi; Jegat, Corinne; Prochazka, Frédéric; Taha, Mohamed
ABSTRACT: Quaternary ammonium‐functionalized polymers (QAFPs) based on branched structures of poly(lactic acid) (PLA) and polycaprolactone (PCL) were blended with neat matrices of PLA and PCL to improve their processability in the melt phase at 160 °C. Different formulations were prepared by varying the proportions of the components of the blends (0, 10, 20, 50, and 60 wt % of QAFP). The rheological behavior of each component and their blends was studied at 160 °C and dynamic mechanical analyses were carried out. The thermal properties of the matrices were also investigated by thermogravimetric analyses and differential scanning calorimetry; they were found to be affected by the presence of QAFPs within them. All the studied blends had a dispersed morphology, highlighted by scanning electron microscopy. The water contact angle of the blends was studied and showed that the hydrophilicity of the surfaces of the blends increased by increasing their QAFP content. The biodegradability of both the components and the blends was investigated: a decrease of the biodegradation kinetics was observed due to the presence of the quaternary ammonium groups, but the materials remain biodegradable. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45261. Abstract :